Scientific Article Writing Workshops for Students Indonesian Language Education Master Program FKIP Tanjungpura University - Sesilia Seli; Martono Martono; Christanto Syam; Patriantoro Patriantoro; A. Totok Priyadi; Natalia Rosi Heavenlim; Anggi Putri Pratiwi; Dyoty Auliya Vilda Ghasya; Y. Touvan Juni Samodra; Uray Gustian; Rio Pranata; Lily Thamrin; Asriah Nurdini; Dian Miranda; Putri Tipa Anasi; Dwi Riyanti; Isti dwi puspita wati (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2023)
This Community Service aims to provide knowledge and skills to Indonesian Language Education Masters Study Program students in writing scientific articles. This activity must be carried out because students must publish their research articles in accredited national journals or international journals under the Regulation of the Minister of Research, Technology, and Higher Education Number 50 of 2018. This activity uses the problem-solving method to overcome three problems, preparation of training modules, implementation workshops/training, and the ability of students to write scientific articles. This community service activity produces the following things. (1) Availability of scientific article writing training modules. (2) The implementation of the workshop/training was well proven by > 75% (16 people/76.19%) of students, who managed to get an average score of 76.19 in a pretty good category. (3) The ability to write scientific articles for students is at an average score of 76.19 in a fairly good category. The average score based on the indicator of completeness of the structure is 83.33 in the good category; the language aspect indicator is 77.38 in a fairly good category; the template suitability indicator of 76.19 in a pretty good category; the Mendeley application utilization indicator is 50.00 in the less category. The scientific article content indicator is 92.86 in the very good category and the literature review indicator of 77.38 in the fairly good category.